Microscopy data, analysis code, and segmentation models for Phenotypic drug susceptibility testing for Mycobacterium tuberculosis variant bovis BCG in 12-hour - Tran, Buu Minh; Larsson, Jimmy; Grip, Anastasia; Karempudi, Praneeth; Elf, Johan (Uppsala University, 2025)
The study aimed to improve the speed of drug susceptibility testing for tuberculosis (TB), particularly drug-resistant strains. Current phenotypic drug susceptibility testing (pDST) methods take at least two weeks. This study used microfluidic chips, microscopy, and deep neural network algorithms to monitor the growth of Mycobacterium bovis Bacillus Calmette–Guérin (BCG) and Mycobacterium smegmatis in the presence of antibiotics. The findings suggest that pDST for TB could potentially be completed in less than 12 hours for slow-growing mycobacteria, offering a significant improvement in diagnosing drug-resistant TB. The entry contains raw microscopy data, analysis code and output, and code to generate figures.
Keywords: Infectious agents; Bacteriology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi